Use of Multimedia Message Service Technology in the Operation Theatre: A Case Report - Anurag Tewari; Ripul Oberoi; Shuchita Garg; Harpreet Kaur; Dinesh Sood; Sunil Katyal (Indian Journal of Anaesthesia, 2008)
The use of mobile phones has long been controversial in the operation theatres citing various incidences wherein aberration of the electronic equipments has occurred due to their use. We hereby report a case where we used mobile phone to capture a dysrrhythmia occurring intra-operatively in a patient via multimedia messaging service (MMS) technology, and sending it to the consultant in charge and a cardiologist via multimedia messaging service(MMS technology) and taking immediate remedial action.